INTEGRATION OF THE CONCEPTS OF GROWTH AND ‎DEVELOPMENT OF STUDENTS IN THE ISLAMIC ‎PSYCHOPEDAGOGICAL PERSPECTIVE - Hidayat, Muhammad; Delliani, Nurfarida; Batubara, Juliana (International Journal of Multidisciplinary Reseach, 2025)
The growth and development of students encompass biological, cognitive, socio emotional, and motor aspects that interact to influence learning abilities. Disparities in these developmental processes have become more evident due to external factors such as the pandemic, nutritional status, physical activity, and socioeconomic conditions. The impact of post pandemic learning loss remains a major challenge in education, particularly in developing countries like Indonesia. Meanwhile, the Merdeka Curriculum provides flexibility for schools to adapt learning to students’ needs, yet its implementation is often not fully grounded in scientific understanding of child development. Therefore, a more developmentally responsive classroom model is needed one that integrates students’ biological, cognitive, and social aspects to create a more inclusive, adaptive, and effective learning process.